Bacterial Community Dynamics in Oil-Contaminated Soils in the Hyper-Arid Arava Valley - Varsik Martirosyan; Ilan Stavi; Tirza Doniger; Itaii Applebaum; Chen Sherman; May Levi; Yosef Steinberger (Agronomy)
Petroleum pollution has become a substantial challenge in soil ecology. The soil bacterial consortia play a major role in the biodegradation of petroleum hydrocarbons. The main objective of this study was to assess changes in bacterial composition and diversity in oil-contaminated dryland soils. The Illumina MiSeq high-throughput sequencing technique was used to study the bacterial diversity and structural change in hyper-arid oil-contaminated soil in the Arava Valley of Israel. The diversity and abundance of soil bacteria declined significantly following oil pollution. The dominant phyla in the petroleum-contaminated soils were Proteobacteria (~33% higher vs. control soil) and Patescibacteria (~2.5% higher vs. control soil), which are oil-associated and hydrocarbon-degrading bacteria. An opposite trend was found for the Actinobacteria (~8%), Chloroflexi (12%), Gemmatimonadetes (3%), and Planctomycetes (2%) phyla, with the lower abundances in contaminated soil vs. control soil. Investigation of long-term contaminated sites revealed significant genus-level taxonomic restructuring in soil bacterial communities. The most evident changes were observed in Mycobacterium, Alkanindiges, and uncultured bacterium-145, which showed marked abundance shifts between spill and control soils across decades. Particularly, hydrocarbon-degrading genera such as Pseudoxanthomonas demonstrated persistent dominance in contaminated sites. While some genera (e.g., Frigoribacterium, Leifsonia) declined over time, others—particularly Nocardioides and Streptomyces—exhibited substantial increases by 2014, suggesting potential ecological succession or adaptive selection. Minor but consistent changes were also detected in stress-tolerant genera like Blastococcus and Quadrisphaera. The effect of oil contamination on species diversity was greater at the 1975 site compared to the 2014 site. These patterns highlight the dynamic response of bacterial communities to chronic contamination, with implications for bioremediation and ecosystem recovery. The study results provide new insights into oil contamination-induced changes in soil bacterial community and may assist in designing appropriate biodegradation strategies to alleviate the impacts of oil contamination in drylands.